The principle of operation as a procedural tool of administrative jurisdiction - Vitalia Boriakina (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право», 2023)
Introduction. By its very nature, administrative proceedings can be considered the main tool for protecting the rights and interests of individuals and legal entities in the public legal field against violations by subjects of authority. Such protection must be based on a fair, impartial and timely hearing. A legal and well-founded decision of the court, which resolves the dispute on the merits, may lose its significance or significantly reduce its importance for the protection of the rights of the individual, if it is adopted with an unreasonable delay. The main direction in the development of the modern administrative process in most countries of the world is characterized by the optimal ratio of the procedural activities of the parties and the court. The classic model of competitiveness is inferior to another model, the essence of which is the implementation of the ideas of judicial economy.